Trends in political science research: Confucian political thought - Marrafa, P. A. C. da S. (International Political Science Abstracts, 2025)
In recent years, there has been an increase in research on Confucian political thought and its influence on East Asia. Recent contributions to the scholarship have explored its fundamental philosophies and ethical principles, highlighting their enduring influence on socio-political thought and raising critical perspectives and questions, such as: Is it possible to create a Confucian democracy? How can a country wage war if Confucianism ultimately advocates peace and harmony due to its moralistic governance? Furthermore, what exactly does an international perspective on the world entail when viewed through a Confucian lens? This article aims to clarify the role of Confucianism in contemporary thought and its persistent impact on modern ethical structures and models of governance. It reviews contemporary ideas related to Confucian principles and encourages further research on their adaptation to address the moral and social challenges of today’s globalized world.